2004
DOI: 10.1097/01.alc.0000127410.84505.2a
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing and Precipitating Factors for Suicide Among Alcoholics: Empirical Review and Conceptual Integration

Abstract: Alcohol dependence is a potent risk factor for suicide. Accordingly, alcoholics should be targeted in suicide prevention efforts. This article reviews the literature on suicide among alcoholics and provides a model that may inform research, clinical work, and prevention efforts. In this model, we propose that aggression/impulsivity, severe alcoholism, negative affect, and hopelessness are key predisposing factors for suicide among alcoholics. We propose that major depressive episodes and stressful life events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 123 publications
9
111
1
10
Order By: Relevance
“…In a prior study, Simon and colleagues (2001) reported that 40% of all suicide attempts in their sample were impulsive. Others have highlighted the potential role of alcohol use as an important component of impulsive suicidal behaviors (Conner, 2004;Conner and Duberstein, 2004). The rate of impulsive suicide attempts among those with a lifetime suicide attempt in the present sample of 62% likely reflects the severity of alcohol dependence in this sample.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a prior study, Simon and colleagues (2001) reported that 40% of all suicide attempts in their sample were impulsive. Others have highlighted the potential role of alcohol use as an important component of impulsive suicidal behaviors (Conner, 2004;Conner and Duberstein, 2004). The rate of impulsive suicide attempts among those with a lifetime suicide attempt in the present sample of 62% likely reflects the severity of alcohol dependence in this sample.…”
Section: Discussionmentioning
confidence: 64%
“…As noted earlier, Conner and colleagues have highlighted the strong overlap between alcohol use, impulsivity, and suicide risk (Conner, 2004;Conner and Duberstein, 2004). Much of this research is understandably focused on understanding and modeling risk for suicidality.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 In accordance with the literature, the risk of suicide in males with substance use disorder was significantly higher if coexisting affective disorder was present. 29,30 This was not the case among females, possibly due to a type II error.…”
Section: J Clin Psychiatry 76:2 February 2016mentioning
confidence: 91%
“…Knowing a person who has attempted suicide, whether a relative or not, has also been reported to be a risk factor for suicidal behavior in mid-life (66). It is possible, though, that exposure to suicidal behavior is the result of "assortative friendships," insofar as friends of individuals with psychological difficulties are more likely to have mental disorder themselves.…”
Section: Imitationmentioning
confidence: 99%